Ability of host discrimination and interspecific competition of Oomyzus sokolowskii (Kurdjumov) - LI Qing-bao; SHI Zu-hua; LIU Shu-sheng (浙江大学学报. 农业与生命科学版)
Oviposition behavior of Oomyzus sokolowskii (Kurdjumov) to the Plutella xylostella (L.) larvae parasitized previously by Cotesia plutellae (Kurdjumov) and its development in the multiparasitized host larvae were investigated in laboratory at 25℃. O. sokolowskii could oviposit into host larvae previously parasitized by C. plutellae, resulting in occurrence of multiparasitized hosts. The parasitism rates of the C. plutellae-parasitized larvae by O. sokolowskii reduced greatly with hatch of C. plutellae eggs inside the hosts. O. sokolowskii could also directly oviposit into old larvae of C. plutellae developed inside the host larvae, leading to occurrence of the hyperparasitized hosts. The hyperparasitism rates tended to increase with age of immature C. plutellae. No O. sokolowskii in the multiparasitized host larvae could survive to adulthood. However, O. sokolowskii in the hyperparasitized host larvae was able to complete their development and emerge from the cocoons of C. plutellae. O. sokolowskii preferred parasitizing unparasitized host larvae when exposed to unparasitized (healthy) and parasitized host larvae simultaneously, suggesting that O. sokolowskii could discriminate the healthy from the parasitized host larvae.